A rare case of lymphoepithelial carcinoma of the parotid gland - Ling, Xiu Ngui; Abdullah, Maizaton Atmadini; Chiun, Kian Chai; Gopalan, Shashi (Ministry of Health, Brunei Darussalam, 2016)
Lymphoepithelial carcinoma (LEC) of salivary gland is uncommon and accounts for 0.4% of malignant salivary gland tumours. Diagnosis can be difficult. We report case describes a 43-year-old indigenous gentleman who presented with a year history of left parotid swelling. Fine needle aspiration was inconclusive and computed tomography of neck was consistent with a benign parotid lesion. The patient proceeded with surgery and histopathology revealed LEC. Adjuvant radiotherapy was given and no recurrence was detected during his two years follow up. Our case highlights that diagnosis of LEC can be difficult and surgical resection or tissue sampling other than fine needle aspiration may need to be considered to make a diagnosis.